Analisis Pengaruh Pembelajaran Tematik Berbasis Proyek Untuk Meningkatkan Kreativitas Siswa SD - Marlin, Adinda Agesti; Afandi, Yogi; Syahfitri, Alda; Madani, Wisti; Kusuma W, Cleo Ratih; Zahara, Chacha Febryan; Muhtarom, Taufik (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the impact of implementing project-based thematic learning on enhancing the creativity of elementary school students. The method employed is a Systematic Literature Review (SLR) by examining five research articles published in nationally accredited journals from 2015 to 2025. The primary data sources are secondary data in the form of previous research articles, obtained through a systematic search using Google Scholar and other academic databases. Data collection was carried out by selecting articles based on the keywords